2020
DOI: 10.1371/journal.pone.0232159
|View full text |Cite
|
Sign up to set email alerts
|

Effect of germination environment on the biochemical compounds and anti-inflammatory properties of soybean cultivars

Abstract: In this study, we investigated changes in the isoflavone content, total phenolic content (TPC), total flavonoid content (TFC), antioxidant activities (DPPH, ABTS), and anti-inflammatory activities of small-seeded and large-seeded soybean cultivars during germination (light/dark conditions). Total isoflavone content was higher at the seed stage in largeseeded soybeans, while it increased after 7 days of germination in small-seeded soybeans, particularly in response to light conditions, under which they had high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
18
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 25 publications
3
18
0
Order By: Relevance
“…The TPC level in taekwangkong (4.18 ± 0.24 mg GAE/g) found in this study was close to the TPC level reported by Ku et al (~3.89 GAE/g) [ 41 ] and Lee et al (3.70 mg GAE/g) [ 42 ] for the same cultivar. In a later study, Eum et al [ 43 ] showed that germination of this cultivar for 3 to 7 days in the dark could help to enhance its TPC level.…”
Section: Resultsmentioning
confidence: 99%
“…The TPC level in taekwangkong (4.18 ± 0.24 mg GAE/g) found in this study was close to the TPC level reported by Ku et al (~3.89 GAE/g) [ 41 ] and Lee et al (3.70 mg GAE/g) [ 42 ] for the same cultivar. In a later study, Eum et al [ 43 ] showed that germination of this cultivar for 3 to 7 days in the dark could help to enhance its TPC level.…”
Section: Resultsmentioning
confidence: 99%
“…Sprouts of grain legume crops can be improved through varietal selection [ 66 ]. There has been extensive research conducted on soybean sprouts improvement, including breeding and genetic improvement [ 66 , 67 , 68 ]. To our knowledge, this is the first study reporting on genomic regions associated with carotenoid content in cowpea sprouts.…”
Section: Discussionmentioning
confidence: 99%
“…Truong et al [20] stated that anti-inflammatory activities of foods might be due to the higher phenolic and flavonoid content. Contrary, Eum et al [11] claimed that bioactive factors such as antioxidant activity, TFC, and TPC do not necessarily reflect the anti-inflammatory properties but the aglycones (such as genistein and daidzein) are more effective. However, we found higher bioactive factors, genistein, daidzein, naringenin, p-coumaric acid, and (+)-catechin (Table 1 and heat map) in BS2 sprouts that showed the highest inhibition of inflammatory factors.…”
Section: Plos Onementioning
confidence: 96%
“…Germination of black soybean can activate the seed metabolites and induce hydrolysis of highmolecular-weight polymers via the activity of enzymes. It triggers the functional activity by enhancing the phytochemicals, including polyphenolic, and non-polyphenolic compounds, amino acids, GABA, and vitamins [11].…”
Section: Introductionmentioning
confidence: 99%